Efektivitas Penerapan Metode Pembelajaran Learning Start With a Question (LSQ) dalam Upaya Meningkatkan Hasil Belajar Peserta Didik Kelas IX SMP Negeri 3 Halmahera Utara - Utubira, Everd Elseos Martin; Lana, Kartini (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2024)
This research was carried out by applying the Learning Start With a Question learning method. The purpose of this study is to improve the learning outcomes of grade IX students in the Science Physics subject. The type of research used in this study is Classroom Action Research (PTK) where the measurement of learning outcome tests and documentation is the technique used in data collection in this study. The results showed that the learning outcomes of students before taking action were 59.7 which was included in the low category. After the first suklus action, the learning outcomes of students increased gradually, namely at 66 and the second cycle was 86.1. From the implementation of these actions, it can be concluded that the application of the Learning Start With a Question (LSQ) learning method can improve student learning outcomes. This is because before the action was taken, the learning outcomes of students were very low and included in the poor category, but after the action was taken, the learning outcomes of students experienced a significant increase in cycles per cycle.